PENGARUH SERTIFIKASI TERHADAP KOMPETENSI DAN INOVASI PEMBELAJARAN GURU MADRASAH IBTIDAIYAH - mundir, mundir mundir (IJIT: Indonesian Journal of Islamic Teaching, 2018)
The purpose of this study was to determine the differences in pedagogical, personality, social, professional competencies, and learning innovation between teachers who had passed the certification program and those who had not yet graduated. With a quantitative approach and ex post facto comparative research, the results show that there are significant differences in aspects of pedagogical, personality, professional, and learning innovation (but not on aspects of social competence) between those who have passed the certification program and those who have not graduated.